Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.2486/indhealth.40.260
|View full text |Cite
|
Sign up to set email alerts
|

Level of Silica in the Respirable Dust Inhaled by Dental Technicians with Demonstration of Respirable Symptoms.

Abstract: Dental technicians are exposed to various dusts in working laboratories. This study was conducted to measure level of silica in the respirable dust generated from dental fixed prosthodontics manufacturing processes using Fourier Transform Infrared Spectroscopy (FTIR), and to compare their occurrence of respiratory symptoms with that of non-dental hospital workers (control group). Respirable dusts were personally sampled from dental technicians working at dental laboratories in Seoul Korea according to NIOSH Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…To the best of our knowledge, the present study had the largest case series reported in dental technicians and evaluated the risk factors through the comparison of the characteristics of the cases with (N = 90) and without (N = 803) DTP. The level of inhalable dust and the concentration of the substances in the dusts show variation among working fields [27]. Therefore, departments in which dental technicians have been working indicate the level of exposure.…”
Section: Pneumoconiosis In Dental Technicians O R I G I N a L P A P Ementioning
confidence: 99%
“…To the best of our knowledge, the present study had the largest case series reported in dental technicians and evaluated the risk factors through the comparison of the characteristics of the cases with (N = 90) and without (N = 803) DTP. The level of inhalable dust and the concentration of the substances in the dusts show variation among working fields [27]. Therefore, departments in which dental technicians have been working indicate the level of exposure.…”
Section: Pneumoconiosis In Dental Technicians O R I G I N a L P A P Ementioning
confidence: 99%
“…Materials contained in dental ceramics are kaolin and feldspar (K2O-Al2O3.SiO2) on build-up, polishing and finishing processes, which can be a source of spread of silica dust in room. 9 Similarly, Figure 1 depicts how silica spread at all points 1, 2 and 3 in the dental laboratory spaces I and II.…”
Section: Discussionmentioning
confidence: 99%
“…Silica exposure may occur during casting, crushing, sanding, porcelain grinding, and polishing in dental laboratories. In a study examining dental laboratories, the concentration of respirable silica dust in the polishing section was double that in the porcelain section, and respiratory symptoms were significantly more frequent in dental technicians than in controls (2).…”
Section: Discussionmentioning
confidence: 99%
“…Pneumoconiosis can develop in dental technicians exposed to metal dust and silica particles in the laboratory (1)(2)(3). Dental technician pneumoconiosis (DTP) is a formerly unknown disorder among technicians and may manifest with sputum and dyspnea symptoms, parenchymal opacities, and decreased respiratory function (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%